DEVELOPMENT OF MATHEMATICS MODULE BASED ON THE SCIENTIFIC APPROACH ON SET MATERIAL FOR CLASS VII - Nunung Azizah; Suparman Suparman (Universitas Ahmad Dahlan, 2018)
Limitations of learning materials is a problem that affects the achievement of learning objectives. Materials that are difficult to understand. Materials that can help students learn actively and independently is a module. This research aims to develop, test the module's feasibility, and know the student response to the development of a mathematics module based on a scientific approach to the set material. The type of research conducted is development research. The subject of research of development mathematics module is material expert, media expert, and some student of SMP Negeri 1 Banguntapan and SMP Muhammadiyah 1 Godean. The object of this research is learning module of mathematics based scientific approach in the material of set for the student of SMP/MTs class VII. The data collection techniques are based on the questionnaire and interviews. The analysis used is quantitative descriptive. The research result shows material expert gives that score of ratings had an average score of 116,67 in perfect criteria score by media expert had an average score of 129 in perfect criteria, and the result of the student response against the module shows that quality module is very good with an average score of 130,80. Based on the calculation, the mathematics module is developed can be used in learning mathematics.